Parental COPD as a Risk Factor for the Development of COPD and Disease Severity in Offspring: A Systematic Scoping Review - Sikjær MG; Klitgaard A; Hilberg O; Løkke A (International Journal of COPD, 2022)
Melina Gade Sikjær,1,2 Allan Klitgaard,1,2 Ole Hilberg,1,2 Anders Løkke1,2 1Department of Medicine, Lillebaelt Hospital, Vejle, Denmark; 2Department of Regional Health Research, University of Southern Denmark, Odense, DenmarkCorrespondence: Melina Gade Sikjær, Department of Regional Health Research, University of Southern Denmark, J.B.Winsløws vej 19, 3, Odense, 5000, Denmark, Email melina.gade.sikjaer@rsyd.dkBackground: There is sparse literature on parental chronic obstructive pulmonary disease (COPD) as a risk factor for the development of COPD in adult offspring, and the impact on disease severity. We aimed to map the literature reporting on the prevalence of and/or association between parental COPD and COPD in offspring, and to evaluate whether or not the literature reports on the severity of COPD or other health-related outcomes in offspring with parental COPD.Methods: A systematic literature search in Embase and Ovid MEDLINE was performed in June 2021. Search terms revolved around COPD and predisposition.Results: Thirteen studies were identified: 10 case–control studies, two cross-sectional studies and one cohort study. Population size varied from 44 to 2668 offspring cases; the distribution of female cases varied from 5% to 80% and mean age ranged from 27 to 65. Nine studies used an antecedents approach and evaluated the prevalence of parental COPD in patients with COPD, which ranged from 19% to 58%. Four studies used a descendants approach, by identifying patients with COPD and subsequently evaluated prevalence of COPD in their offspring, and found a prevalence of 0% to 17%. Apart from one, all the studies found an increased odds ratio for COPD in individuals with parental COPD. Four studies reported on parental smoking history and nine studies reported on smoking history in offspring. Three studies evaluated the association between parental COPD and COPD-related outcomes in patients with COPD.Conclusion: This review indicates that parental COPD is associated with a higher risk of COPD in offspring. The literature is sparse, and we identified a knowledge gap on whether parental COPD is a risk factor for severe COPD and other health conditions in offspring.Keywords: COPD severity, disease predisposition, familial predisposition, family history